A 5-year follow-up study on the efficacy and safety of ultrasound-guided laser ablation in elderly patients with papillary thyroid microcarcinoma: A retrospective, single-center study from China - Juan, Zhang; Yongping, Liang; Han, Xiaochen; Wang, Zhiwu; Liu, Jingping; Zhao, Yongfeng; Liu, Wengang; Zhou, Ping (Frontiers in Endocrinology, 2022)
Objective: To evaluate the long-term efficacy and safety of ultrasound-guided percutaneous laser ablation (PLA) for the treatment of elderly patients with papillary thyroid microcarcinoma (PTMC). Methods: From September 2015 to April 2017, 38 elderly patients with fine needle aspiration biopsy (FNAB) confirmed PTMC were treated with PLA. Before the treatment, the location and volume of the nodule, together with the patients’ symptoms were evaluated. 24 hours after the treatment, contrast-enhanced ultrasound (CEUS) was performed to evaluate the completeness of the ablation. To evaluate the volume of the ablation area and recurrence or metastasis, ultrasound examination was performed at 1, 3, 6, and 12 months after the treatment and every 6 months thereafter. FNAB was performed for any suspicious recurrence or metastasis lesions. Result: The ablation of all the 38 patients were all achieved complete confirmed by CEUS. No obvious complications were found. The success rate of single ablation was 100%. The average follow-up time was 64.58 ± 5.29 months (60 ~ 78 months). By the time of the last follow-up, 31 (81.58%) ablation lesions disappeared completely and 7 (18.42%) ablation lesions showed scar-like changes. The volume of nodules was 40.69 ± 16.45mm3 before operation, which decreased to 0.22±0.76mm3 by the end of 42 months, and all nodules disappeared 4 years after ablation (P < 0.01). At 6, 12, 18, 24, 30, 36, and 42 months after ablation, the average volume reduction rates (VRR) were 12.09%, 31.21%, 50.9%, 72.06%, 84.79%, 95.65%, and 100% respectively. Of all the patients enrolled, one patient (2.6%) had local recurrence and was treated with PLA again. No regrowth of treated nodule or lymph node metastasis and distant metastases were detected. Conclusion: Ultrasound-guided PLA is effective and safe for the treatment of elderly patients with PTMC who are ineligible for surgery.